Designación de tutela y curaduría por los notarios a personas incapaces tanto absolutos como relativos para garantizar sus patrimonios - Castillo Garofalo, Gerardo (2022)
Civil law combines rules and legal principles that regulate the relationship between people or patrimony, so guardianships and conservatorships are part of the judicial institution aimed at the protection and administration of assets of persons who do not have legal capacity, whose designation corresponds to guidelines established in the current regulatory systems. Thus, the objective of this research is to analyze the designation of Guardianship and Conservatorship by Notaries to incapable persons, both absolute and relative, in order to guarantee their patrimonies. In order to achieve this, a qualitative methodology of theoretical, legal and doctrinal triangulation focused on interdiction and guardianship-guardianship applied, at the same time interviews applied to a sample of 3 acting judges, y 3 acting notaries, and legal professionals about the change in the notary functions........